Words on bathroom walls [videorecording (DVD)] - Robb, AnnaSophia, 1993-; Goggins, Walton, 1971-; Russell, Taylor, 1994-; Garcia, Andy; Walton, Julia, 1986- (Roadside Attractions LLC, 2020)
Diagnosed with a mental illness halfway through his senior year of high school, a witty introspective teen struggles to keep it a secret while falling in love with a brilliant classmate who inspires him to open his heart and not be defined by his condition.